The prostate metastasis suppressor gene NDRG1 differentially regulates cell motility and invasion. Issue 6 (2nd May 2017) - Sharma, Anup; Mendonca, Janet; Ying, James; Kim, Hea‐Soo; Verdone, James E.; Zarif, Jelani C.; Carducci, Michael; Hammers, Hans; Pienta, Kenneth J.; Kachhap, Sushant
Abstract : Experimental and clinical evidence suggests that N‐myc downregulated gene 1 ( NDRG1 ) functions as a suppressor of prostate cancer metastasis. Elucidating pathways that drive survival and invasiveness of NDRG1 ‐deficient prostate cancer cells can help in designing therapeutics to target metastatic prostate cancer cells. However, the molecular mechanisms that lead NDRG1 ‐deficient prostate cancer cells to increased invasiveness remain largely unknown. In this study, we demonstrate that NDRG1 ‐deficient prostate tumors have decreased integrin expression and reduced cell adhesion and motility. Our data indicate that loss of NDRG1 differentially affects Rho GTPases. Specifically, there is a downregulation of active RhoA and Rac1 GTPases with a concomitant upregulation of active Cdc42 in NDRG1 ‐deficient cells. Live cell imaging using a fluorescent sensor that binds to polymerized actin revealed that NDRG1 ‐deficient cells have restricted actin dynamics, thereby affecting cell migration. These cellular and molecular characteristics are in sharp contrast to what is expected after loss of a metastasis suppressor. We further demonstrate that NDRG1 ‐deficient cells have increased resistance to anoikis and increased invasiveness which is independent of its elevated Cdc42 activity. Furthermore, NDRG1 regulates expression and glycosylation of EMMPRIN, a master regulator of matrix metalloproteases. NDRG1 deficiency leads to an increase in EMMPRIN expression with a concomitant increase in matrix metalloproteases and thus invadopodial activity. Using a three‐dimensional invasion assay and an in vivo metastasis assay for human prostate xenografts, we demonstrate that NDRG1 ‐deficient prostate cancer cells exhibit a collective invasion phenotype and are highly invasive. Thus, our findings provide novel insights suggesting that loss of NDRG1 leads to a decrease in actin‐mediated cellular motility but an increase in cellular invasion, resulting in increased tumor dissemination which positively impacts metastatic outcome. Abstract : N‐myc downregulated gene 1 ( NDRG1 ) is among few known prostate metastasis suppressors. The mechanism by which NDRG1 elicits its metastasis suppressor function remains poorly understood. In this report, we demonstrate that NDRG1‐deficient prostate tumors have decreased Rho GTPase activation, leading to restricted actin dynamics and cell motility. Our novel findings indicate that while NDRG1 deficiency decreases cellular motility, it also increases cellular invasiveness and tumor dissemination through EMMPRIN, a master regulator of matrix metalloproteases.